Empowering Affected Interests (Cambridge University Press, 2025)
Empowering Affected Interests brings together a group of leading contemporary democratic theorists and philosophers to debate a taken-for-granted principle at the heart of the democratic project but increasingly under strain in a global era: the idea all those affected by a decision should be included in the making of that decision.